Pediatric tuberculosis outcomes and factors associated with unfavorable treatment outcomes in Botswana, 2008-2019: a retrospective analysis - Keatlaretse Siamisang; Goabaone Rankgoane-Pono; Tumisang Malebo Madisa; Tantamika Kabamba Mudiayi; John Thato Tlhakanelo; Paul Mubiri; Khutsafalo Kadimo; Francis Msume Banda; Vincent Setlhare (BMC, 2022)
Abstract Introduction Globally, the amount of research on the outcomes of pediatric tuberculosis (TB) is disproportionately less than that of adult TB. The diagnosis of paediatric TB is also problematic in developing countries. The aim of this study was to describe the outcomes of pediatric TB in Botswana and to identify the factors associated with unfavorable outcomes. Methods This was a retrospective analysis of pediatric TB outcomes in Botswana, over a 12-year period from January 2008 to December 2019. Treatment success (treatment completion or cured) was considered a favorable outcome, while death, loss to follow-up and treatment failure were considered unfavorable outcomes. Program data from drug-sensitive TB (DS-TB) cases under the age of 15 years were included. Sampling was exhaustive. Binary logistic regression was used to determine the factors associated with unfavorable outcomes during TB treatment. A p value of < 0.05 was considered a statistically significant association between the predictor variables and unfavorable outcomes. Results The data of 6,004 paediatric TB cases were extracted from the Botswana National TB Program (BNTP) electronic registry and analyzed. Of these data, 2,948 (49.4%) were of female patients. Of the extracted data, 1,366 (22.8%) were of HIV positive patients and 2,966 (49.4%) were of HIV negative patients. The rest of the data were of patients with unknown HIV status. Pulmonary TB accounted for 4,701 (78.3%) of the cases. Overall, 5,591 (93.1%) of the paediatric TB patient data showed treatment success, 179 (3.0%) were lost to follow-up, 203 (3.4%) records were of patients who died, and 31 (0.5%) were of patients who experienced treatment failure. The factors associated with unfavorable outcomes were positive HIV status (AOR 2.71, 95% CI: 2.09-3.52), unknown HIV status (AOR 2.07, 95% CI: 1.60-2.69) and retreatment category (AOR 1.92, 95% CI: 1.30-2.85). Compared with the 0-4 years age category, the 5-9 years (AOR 0.62, 95% CI: 0.47-0.82) and 10-14 years (AOR 0.76, 95% CI: 0.60-0.98) age categories were less likely to experience the unfavorable outcomes. Conclusion This study shows a high treatment success rate among paediatric TB cases in Botswana. The government under the National TB Program should maintain and consolidate the gains from this program. Public health interventions should particularly target children with a positive or unknown HIV status, those under 5 years, and those who have been previously treated for TB.